الطريقة المثلى في تعليم القواعد النحوية للمبتدئين والمتقدمين لغير الناطقين بها: The Ideal Method in Learning Rules of Nahwu for Beginners and Advanced Students for Non-Arabic Speakers - Ronny Mahmuddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aimed to identify and describe the best method of teaching rules of nahwu for beginners and advanced students for foreign speakers (non-Arabic). This research was a qualitative descriptive study with a type of library research by tracing references in data collection. The results of this study indicate that the best method of teaching rules of nahwu for foreign speakers is of two methods, namely: The first one is the aural-oral method (sam'iyyah syafawiyyah) for the beginner level. This method uses patterned training techniques (pattern drill) through activities of istimā' (listening) and kalām (speaking) to form behavior (habits) for beginner-level learners in using language along with learning rules of nahwu through sentence structure (applied nahwu); The second one is the method of al-istiqra'iyyah (inductive method) for advanced students. This method is one that makes the dialogue/reading text the center of learning all language skills, both speaking and reading related to the rules of nahwu by using three training techniques (drill) that do not come out of the dialogue/reading text, namely the pattern drill (patterned training), meaning drill (exercise of the meaning) and communicative drill (communication exercise). These three techniques combine the formation of behavioral habits in using language along with understanding the meaning and ability to communicate with native speakers (Arabs) by paying attention to the theoretical principles of nahwu (nahwu concept) and applied nahwu (applied nahwu).